Efficient access to enantiopure 1,3-disubstituted isoindolines from selective catalytic fragmentation of an original desymmetrized rigid overbred template - Pandey, Ganesh; Varkhedkar, Rajesh; Tiwari, Divya (Organic & Biomolecular Chemistry, 2015)
An efficient and scalable synthesis of various enantiopure 1,3-disubstituted isoindolines is reported. The base catalyzed nucleophilic fragmentation of a rigid overbred template is established with various substrates to afford the corresponding 1,3-disubstituted isoindoline ester, amide, thioate, 1,3-amino alcohol and isoindolylcarboxylic acid. The crucial rigid overbred template is synthesized in an optically pure form in multigram scale by asymmetric desymmetrization of the corresponding meso compound.